Program for calculating the minimum electrical power loss in an asynchronous traction engine of mainline locomotives - Burxanxodjaev A.M. , Karimov R.Ch. *, Usmonov K.K., Iksar E.V. (International Journal of Advanced Science and Technology, 2020)
The article discusses the improvement of traction and energy performance main-line locomotives due to more complete use of possibilities of flexible microprocessor control and efficient algorithm that provides reduction of electrical losses in the traction asynchronous drive over the entire range working capacity